Recovery from exercise: vulnerable state, window of opportunity, or crystal ball? - Luttrell, Meredith J.; Halliwill, John R. (Frontiers in Physiology, 2015)
Why should we study the recovery from exercise as a discrete phenomenon from exercise itself? We identify three distinct (but not mutually exclusive) rationales that drive the need to investigate the physiology of recovery from exercise. 1) Some individuals are at a heightened risk of clinical outcomes in the immediate post-exercise period; thus the potential negative outcomes of this “vulnerable state” must be weighed against the numerous benefits of exercise training, and may be mitigated to reduce risk. 2) Many of the signaling mechanisms responsible for the beneficial effects of exercise training remain amplified during the exercise recovery period, and may present a “window of opportunity” that can be exploited by interventions to enhance the beneficial adaptations to exercise training, especially in clinical populations. 3) On an individual level, exercise recovery responses may provide investigators with a “crystal ball” ability to predict future clinical outcomes even in apparently healthy individuals. In short, the physiology of recovery is a multi-faceted and complex process, likely involving systems and pathways that are distinct from the physiology of exercise itself. For these reasons, it merits ongoing study.